Power line enhancement for data monitoring of neural electrical activity in the human body - Haidar, Ahmed M. A.; C., Sridhathan; Hazza, Abdulsalam; Saleh, Ahmed (Academic Journals, 2011)
Distance and real-time data monitoring are the necessary condition that makes any system in good working order. Recent advancements in micro-electronics and wireless technology enable the application of wireless sensors in both industry and wild environments. However, Long-distance wireless communication has several drawbacks like limited bandwidth, considerable costs and unstable connection quality. Therefore, Power Line Communication (PLC) using pre-established Power Lines (PL) becomes more attractive for high data transmission technology. This paper reviews the existing distance data monitoring systems and presents a case study for data transferring of temperature and heart beat measurement. The simulations were carried out on the detected and transmitted signals of medical data using Matlab program. Furthermore, a framework of Intelligent Neural Monitoring System (INMS) is proposed for future works. The performance of PLC as a channel to transfer the patient Heart Rate (HR) is evaluated based on the Bit Error Rate (BER).